PS5:105 Hdl inhibits t cell proliferation is sle. (21st March 2018) - Fernandes Das Neves, M; Favas, C; Batuca, J; Jury, EC; Alves, José Delgado
Abstract : Purpose: Systemic lupus erythematosus (SLE) is associated with dyslipidemia and increased cardiovascular risk. The SLE pattern is characterised by high plasma levels of low-density lipoproteins (LDL) and triglycerides and low levels of high-density lipoproteins (HDL). HDL is a complex plasma lipoprotein that is recognised for its protective role in atherosclerotic disease. It consists of an outer layer of lipids and apolipoproteins, with apolipoproteinA-1 (apoA-1) constituting 70% of the protein content, a triglyceride and cholesterol ester-rich core, and several enzymes. In addition to its anti-atherogenic properties, mainly associated with reverse cholesterol transport from vessels, HDL has also anti-inflammatory properties that are not clearly understood. This work aims to show the effect of HDL on T lymphocyte proliferation. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from 7 SLE patients, with at least 4 SLICC/ACR classification criteria and normal serum lipid profiles, and 3 healthy donors. PBMCs were cultured with and without HDL (at the concentrations of 50, 300 and 600 µg/mL) before CD3 and CD28 stimulation. After 4 days in culture, T cell proliferation was measured by flow cytometry through Ki-67 staining. Regulator T cells (Tregs) phenotyping (CD4 +CD25+CD27-FoxP3+) was performed. The expression of the cholesterol transporter ABCA1 in T lymphocytes was also measured by flow cytometry. Results: HDL decreased T cell proliferation in a dose-dependent manner, with the biggest effect obtained with the physiologic concentration of 600 µg/mL. The inhibition of T cell proliferation was more pronounced in SLE patients than in the healthy donors. SLE patients tend to have higher baseline T cell proliferation measured by ki-67 expression. There were no differences in the prevalence of Tregs among patients and healthy donors. The expression of ABCA1 on the surface of T lymphocytes was similar between groups. Conclusions: This study is the first demonstration of a regulatory effect of HDL on the adaptive immune system of SLE patients. Here we show that HDL can decrease T cell proliferation, which is not correlated with the expression of the ABCA1, the main cholesterol transporter to ApoA-1. We expect to further elucidate HDL effects on the immune system in future studies.